Fiber-reinforced resin molding having Anti-pathogen property and method for manufacturing the same

JP2025031039APending Publication Date: 2025-03-07TORAY INDUSTRIES INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023136990
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0014】 本発明の繊維強化樹脂成形体は、表面において均質な抗病原体性能を発現させることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025031039000001_ABST
    Figure 2025031039000001_ABST
Patent Text Reader

Abstract

To provide a fiber-reinforced resin molding in which antibacterial property or antiviral property is imparted to its surface, and a method for manufacturing the same.SOLUTION: A fiber-reinforced resin molding contains a reinforcement fiber (A), a matrix resin (B) and a compound (C) having antibacterial property or antiviral property, wherein at least a part of the compound (C) is exposed on the surface of the fiber-reinforced resin molding.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fiber-reinforced resin molding having an antibacterial or antiviral property imparted to the surface. [Background technology]

[0002] Fiber-reinforced plastic molded products have the advantages of being lightweight, strong, and rigid, and are therefore used in a wide range of industrial fields, including electrical and electronic equipment, sports, and mobility such as aircraft. The most common method for manufacturing these fiber-reinforced plastic molded products is to form a preform by laminating a base material called a prepreg, in which reinforcing fibers are impregnated with a matrix resin, to achieve the desired characteristics, and then to heat and press the preform.

[0003] In recent years, against the backdrop of the worldwide spread of infectious diseases, there has been an increasing demand for fiber-reinforced resin moldings with added value such as antibacterial or antiviral properties (collectively referred to as "antipathogenic" in this specification). Examples of such products include the housings of IT equipment that are often touched by multiple users, and X-ray inspection equipment that is in contact with many patients.

[0004] As a method for imparting anti-pathogen properties to fiber-reinforced resin molded bodies, it has been common to add antibacterial or antiviral agents to the matrix resin of the substrate, such as prepreg. However, only a portion of the agent present on the surface of the molded body contributes to the anti-pathogen properties, and most of the other agents are present in the matrix resin, so the additives are used inefficiently. In addition, if the concentration present on the surface is increased to achieve high performance, the concentration of the entire matrix resin must be increased, requiring a large amount of antibacterial or antiviral agent, which not only increases costs but also causes the matrix resin itself to become brittle, resulting in a decrease in the mechanical properties of the molded body.

[0005] Therefore, for example, Patent Documents 1 and 2 disclose a method of coating the surface of a fiber-reinforced resin molded body after molding with an antibacterial coating agent like paint. This method requires a minimum amount of antibacterial agent, solving the problem of additive utilization efficiency. However, coating requires a coating process and a curing process of the antibacterial coating agent after molding of the molded body, which increases manufacturing costs. In addition, with the coating method, the antibacterial agent is prone to falling off after long-term use, and there are also issues with the sustainability of antibacterial performance.

[0006] On the other hand, Patent Document 3 discloses a method in which a thermosetting resin containing an antibacterial agent is applied to the surface of a sheet-shaped fiber reinforced resin material with a brush or applied to the surface of a mold in advance, and an antibacterial agent-containing resin layer is formed at the same time as heating and pressurization. According to this method, an antibacterial agent-containing thermosetting resin is applied to a sheet-shaped fiber reinforced resin material before molding, and molding of the fiber reinforced resin and formation of the antibacterial agent-containing resin layer are performed simultaneously, so that manufacturing time and costs can be reduced compared to coating. In addition, since the thermosetting resin layer containing the antibacterial agent is firmly bonded to the fiber reinforced resin, there is a high possibility that the durability of the antibacterial performance will also be increased. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 11-228908 [Patent Document 2] JP 2023-71243 A [Patent Document 3] JP 2023-54044 A Summary of the Invention [Problem to be solved by the invention]

[0008] Generally, when a thermosetting resin is heated, its viscosity decreases and it becomes easy to flow, and then when the curing reaction starts, its viscosity increases and it hardens. Therefore, in the method described in Patent Document 3, the antibacterial agent-containing thermosetting resin flows together with the antibacterial agent due to the pressure during molding, and the antibacterial agent flows out, which creates a new problem that the manifestation of antibacterial performance is likely to be uneven.

[0009] An object of the present invention is to provide a fiber-reinforced resin molding that exhibits uniform anti-pathogen performance on the surface of the fiber-reinforced resin molding. [Means for solving the problem]

[0010] In order to solve the above problems, the fiber-reinforced resin molding of the present invention is a fiber-reinforced resin molding that includes reinforcing fibers (A), a matrix resin (B), and a compound (C) having antibacterial or antiviral properties, and has an anti-pathogenic region in which at least a portion of the compound (C) is exposed on the surface of the fiber-reinforced resin molding.

[0011] Another aspect of the present invention is a method for producing a composite material comprising the steps of: preparing an intermediate substrate comprising reinforcing fibers (A) and a matrix resin (B); A step of obtaining a preform having a dispersion of a compound (C) having antibacterial or antiviral properties disposed on the surface of the intermediate substrate by the following method (I) or (II); (I) A dispersion obtained by dispersing the compound (C) in a solvent having a solubility in the matrix resin (B) is adhered to at least a part of the surface of the intermediate substrate.

[0012] (II) A sheet substrate containing the thermoplastic resin (D) having the compound (C) adhered thereto is laminated onto at least a portion of the surface of the intermediate substrate.

[0013] a step of molding the preform by heating and pressing; The present invention relates to a method for producing a fiber-reinforced resin molded body. Effect of the Invention

[0014] The fiber-reinforced resin molding of the present invention can exhibit uniform anti-pathogen performance on the surface.

[0015] The method for producing a fiber-reinforced resin molding of the present invention can suppress the outflow of compounds having anti-pathogenic properties due to the application of heat and pressure during molding, thereby enabling the surface of the fiber-reinforced resin molding to express uniform anti-pathogenic performance. [Brief description of the drawings]

[0016] [Figure 1] 1 is a schematic diagram showing an overall image of a fiber-reinforced resin molding of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing an embodiment of a fiber-reinforced resin molding of the present invention that does not contain a thermoplastic resin (D). [Diagram 3] FIG. 2 is a schematic cross-sectional view showing a method for measuring the distance between the compound (C) and the reinforcing fibers in an example of the present invention. [Figure 4] FIG. 2 is a schematic cross-sectional view showing an embodiment of a fiber-reinforced resin molded product of the present invention in which a thermoplastic resin (D) is exposed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The fiber-reinforced resin molding of the present invention will be described below with reference to the drawings as appropriate. However, the present invention is not limited to the specific embodiment shown in the drawings, and the description of the specific embodiment shown in the drawings can also be understood as a description of the present invention as a higher-level concept.

[0018] Fig. 1 is a schematic perspective view showing an overall image of a fiber-reinforced resin molding of the present invention. As shown in Fig. 1, the fiber-reinforced resin molding of the present invention has an antipathogenic region 2 described below on at least a part of its surface.

[0019] As shown in Fig. 2, the fiber-reinforced resin molding 1 of the present invention includes reinforcing fibers (A) 3, a matrix resin (B) 4, and an antibacterial or antiviral compound (C) 5. In this specification, the matrix resin (B) refers to a resin that mainly constitutes the region in which the reinforcing fibers (A) are embedded, that is, a resin that occupies the largest region among the resins in contact with the reinforcing fibers (A). In an embodiment including a thermoplastic resin (D) described later, even if a part of the thermoplastic resin (D) is in contact with the reinforcing fibers (A), the thermoplastic resin (D) is not considered to be a part of the matrix resin (B).

[0020] The type of reinforcing fiber (A) is not particularly limited, and for example, inorganic fibers such as carbon fiber and glass fiber, organic fibers such as aramid fiber, or natural fibers can be used, and one or more of these may be used in combination. Among them, PAN-based or pitch-based carbon fibers, which have high specific strength and specific rigidity, are particularly preferably used. In addition, from the viewpoint of the balance between strength and economy, it is also preferable to use carbon fiber and glass fiber in combination, and from the viewpoint of the balance between strength and impact resistance, it is also preferable to use carbon fiber and organic fiber in combination.

[0021] As the form of the reinforcing fiber (A), continuous fibers that exist without being broken in the molded product are preferred from the viewpoint of efficiently exhibiting the effect of improving mechanical properties. Examples of the form of the continuous fiber include a form in which the fibers are aligned in one direction and a woven form in which fiber bundles are woven together. In addition, from the viewpoint of shape conformity, a form of discontinuous fibers in which the fibers are broken in the molded product is preferred. Examples of the form of the discontinuous fiber include a form in which the fibers are aligned in one direction in a bundle, a state in which the fibers are randomly dispersed in a bundle, and a state in which the fibers are opened to a state of approximately monofilament and randomly dispersed. Here, approximately monofilament refers to a state in which the single yarns of the discontinuous fiber exist in a fineness strand of less than 500 fibers.

[0022] The type of matrix resin (B) is not particularly limited, and either a thermosetting resin or a thermoplastic resin can be used, and a resin in which a plurality of types of thermosetting and / or thermoplastic resins are mixed may also be used. In this specification, if the main component of the matrix resin components (a component that accounts for more than 50% by weight when the entire resin components constituting the matrix resin are taken as 100% by weight), it is called a thermoplastic resin, and if it is a thermosetting resin, it is called a thermosetting resin.

[0023] The compound (C) having anti-pathogenic properties may be an organic compound having a chemical structure compatible with the matrix resin, but is preferably a particulate compound. Such a particulate compound is preferably a metal compound (c). Here, the metal compound (c) is an inorganic compound or metal oxide carrying a metal ion. More preferably, the compound (C) is an inorganic compound carrying a metal ion, that is, an inorganic support carrying an anti-pathogenic metal ion. Examples of inorganic supports include zeolite, clay minerals, glass, silica gel, alumina, zirconium phosphate, and calcium phosphate. Examples of anti-pathogenic metal ions include silver ions, copper ions, and zinc ions. Moreover, as the metal oxide, cerium oxide is particularly preferred. Cerium oxide is preferably composed of a mixture of Ce2O3 and CeO2, and more preferably has a structure in which a mixture of Ce2O3 and CeO2 is used as a central core, and a polymer layer is formed on the surface of the core, the polymer layer being coated with various polymers.

[0024] In the fiber-reinforced resin molded product of the present invention, at least a part of the compound (C) is exposed on the surface. "At least a part is exposed" means that when the surface is scanned by X-ray photoelectron spectroscopy (XPS: X-ray Photoelectron Spectroscopy), 0.1 atomic % or more of an element derived from the compound (C) can be detected. The compound (C) does not need to be exposed on the entire surface of the fiber-reinforced resin molded product, and it is sufficient that the compound (C) is exposed in a part where anti-pathogenicity is required. From the viewpoint of minimizing the amount of compound (C) used, it is preferable that the compound (C) is exposed on a part of the surface of the fiber-reinforced resin molded product. Hereinafter, in this specification, the area where the compound (C) is exposed when the surface of the molded product is viewed is referred to as "anti-pathogenic area". In the molded product of the present invention, the anti-pathogenic area is typically formed in a part that frequently comes into contact with the user or patient.

[0025] In the cross section (cross section perpendicular to the surface) of the antipathogenic region, it is preferable that 50 to 100% of the total amount of compound (C) is present within 100 μm from the surface of the molded article. By adopting such an embodiment, it is possible to efficiently impart antipathogenic performance while reducing the amount of compound (C) added. Here, the presence ratio of compound (C) within a range of 100 μm from the surface of the molded article can be measured from an element mapping image prepared by scanning electron microscope-energy dispersive X-ray spectrometry (SEM-EDX) in an arbitrary cross section of the fiber-reinforced resin molded article, and specifically, it can be measured by the method described in the examples described later.

[0026] In the fiber-reinforced resin molding of the present invention, the distance between the compound (C) exposed from the matrix resin (B) and the reinforcing fiber (A) in the cross section of the antipathogenic region is preferably 0.05 μm or more and 5.00 μm or less from the viewpoint of suppressing the falling off of the compound (C) and enhancing the durability of the antipathogenic property. By making the distance between the compound (C) and the reinforcing fiber (A) 5.00 μm or less, the outflow of the compound (C) during the formation process of the matrix resin (B) can be suppressed, and uniform antipathogenic property is easily expressed. Here, the distance between the compound (C) and the reinforcing fiber (A) can be defined as the distance from the surface of the compound (C) to the surface of the reinforcing fiber (A) on the dotted line α connecting the centroid of the compound (C) and the centroid of the reinforcing fiber (A) observed in an arbitrary cross section, as shown in FIG. 3. As a measurement method, a method of measuring from an element mapping image prepared by SEM-EDX can be mentioned. In this case, the reinforcing fiber (A) refers to the reinforcing fiber closest to the compound (C) to be measured, and the method for identifying the compound (C) to be measured is to target the compound within a range of 10 μm in the thickness direction from the surface of the fiber-reinforced resin molded body (FIG. 3). Specifically, the average value of the distance measured by the method described in the examples below is taken as the distance between the compound (C) and the reinforcing fiber (A).

[0027] In the fiber-reinforced resin molding of the present invention, in the antipathogenic region, the dropout rate of the compound (C) after testing in accordance with JIS H 8504 (1999) is preferably 5% or less. By adopting such an embodiment, the dropout of the compound (C) due to washing or rubbing is suppressed, and the durability of the imparted antipathogenic performance is improved. Here, the test in accordance with JIS H 8504 (1999) refers to the "tape test method" in the "plating adhesion test method." The dropout rate is calculated using the following formula. Dropout rate [%] = (amount of compound (C) before test - amount of compound (C) after test) / (amount of compound (C) before test) x 100 The amount of compound (C) is expressed as the concentration (atomic %) of the element derived from compound (C) detected when the surface is scanned by XPS.

[0028] From the viewpoint of stable expression of antipathogenicity and obtaining a molded product with good appearance, the antipathogenic region of the fiber-reinforced resin molded product of the present invention may be in an embodiment in which a thermoplastic resin (D) 6 other than the matrix resin (B) is exposed together with the compound (C). It is preferable that such a thermoplastic resin (D) is unevenly distributed within a range of 100 μm from the surface. In a molded product of such an embodiment, it becomes easy to suppress the flow of the matrix resin (B) during molding, and it becomes easy to suppress the outflow of the compound (C).

[0029] When the matrix resin (B) is a thermosetting resin, the type of the thermoplastic resin (D) is not particularly limited. When the matrix resin (B) is a thermoplastic resin, the above-mentioned effect can be significantly exhibited by making the thermoplastic resin (D) have a melting point higher than that of the matrix resin (B).

[0030] Furthermore, it is preferable that a layer consisting of the compound (C) and the thermoplastic resin (D) is formed on the surface of the antipathogenic region. In this case, when the thermoplastic resin (D) is at least partially in contact with the reinforcing fiber (A) near the boundary between the antipathogenic region and the layer containing the matrix resin (B), peeling of the layer can be suppressed and the durability of the antipathogenic property can be improved.

[0031] It is also possible to form a layer in which the thermoplastic resin (D) is present in the form of a nonwoven fabric on the surface of the antipathogenic region. In this case, the compound (C) can be supported on the surface of the nonwoven fabric, which can more effectively suppress the flow of the compound (C) and increase the durability of the antipathogenic property.

[0032] The antipathogenic region preferably has a log reduction in infectivity measured in accordance with ISO 21702 of 1.0 or more, more preferably 2.0 or more. In this embodiment, when focusing on antiviral properties, the effect of inactivating viruses is prominent, and excellent performance is exhibited. The log reduction in infectivity can be measured by the method described in the Examples below.

[0033] As an example, the fiber reinforced resin molding of the present invention is Providing an intermediate substrate comprising reinforcing fibers (A) and a matrix resin (B); A step of obtaining a preform having a dispersion of a compound (C) having antibacterial or antiviral properties disposed on the surface of the intermediate substrate by the following method (I) or (II); (I) A dispersion obtained by dispersing the compound (C) in a solvent having a solubility in the matrix resin (B) is adhered to at least a part of the surface of the intermediate substrate. (II) A sheet substrate (D) containing a thermoplastic resin having the compound (C) adhered thereto is laminated onto at least a portion of the surface of the intermediate substrate. a step of molding the preform by heating and pressing; The film can be produced by a manufacturing method having the steps:

[0034] In the step of preparing the intermediate substrate, it is preferable to laminate a plurality of intermediate substrates containing the reinforcing fiber (A) and the matrix resin (B), but it is also acceptable to use only one intermediate substrate. The form of the reinforcing fiber (A) is as described above, and two or more different types of intermediate substrates may be laminated in combination.

[0035] The first method (I) for obtaining a preform in which a dispersion containing compound (C) is disposed on the surface of an intermediate substrate is a method in which a dispersion in which compound (C) is dispersed in a solvent having solubility in matrix resin (B) is adhered to at least a portion of the surface of the intermediate substrate, i.e., the surface that forms the anti-pathogenic region.

[0036] Here, the solvent having the ability to dissolve the matrix resin (B) may be one in which at least a part of the matrix resin (B) dissolves. Here, the solvent in which at least a part of the matrix resin (B) dissolves can be selected with the HSP distance between the matrix resin (B) and the solvent being 8 or less as an index. By dissolving at least a part of the matrix resin (B) in the solvent, the compound (C) becomes partially embedded in the matrix resin (B), and in the subsequent molding step of heating and pressing, the outflow of the compound (C) can be suppressed, and excellent anti-pathogen performance can be exhibited.

[0037] Methods for adhering the dispersion to the surface of the intermediate substrate include a method of applying the dispersion with a brush and a method of spraying the dispersion using a spray. From the viewpoint of achieving uniform adhesion, the method of spraying the dispersion using a spray is preferred.

[0038] The second method (II) for obtaining a preform in which a dispersion containing compound (C) is disposed on the surface of an intermediate substrate is a method in which a sheet substrate containing thermoplastic resin (D) having compound (C) adhered thereto is laminated on at least a portion of the surface of the intermediate substrate.

[0039] The sheet substrate containing the thermoplastic resin (D) is not particularly limited in its form, but a film-like or nonwoven fabric-like substrate can be preferably used. Among them, a nonwoven fabric-like substrate is preferred in terms of shape conformability when heated and pressed, and efficient surface support of the compound (C). The sheet substrate containing the nonwoven fabric-like thermoplastic resin (D) is particularly preferred in terms of suppressing the dropping off of the compound (C) by melting when heated and pressed to form a layer on the surface of the fiber-reinforced resin molded product and impregnating the reinforcing fiber (A). In addition, the sheet substrate containing the nonwoven fabric-like thermoplastic resin (D) does not have to melt when heated and pressed, since it can exert its effect as long as the compound (C) can be efficiently supported on the surface.

[0040] The preform thus formed is heated and pressurized to form a fiber-reinforced resin molding. As the method of heating and pressing, a known method such as press molding or autoclave molding can be used, but press molding is preferred from the viewpoint of shortening the production cycle time. EXAMPLES

[0041] The present invention will be described in more detail below with reference to examples, although the scope of the present invention is not limited to these examples in any way.

[0042] [material] <Thermosetting resin (b-1)> 30 parts by mass of "jER (registered trademark)" 828 (manufactured by Mitsubishi Chemical Corporation), 20 parts by mass of "jER (registered trademark)" 1001 (manufactured by Mitsubishi Chemical Corporation), 15 parts by mass of "jER (registered trademark)" 1007 (manufactured by Mitsubishi Chemical Corporation), and 35 parts by mass of "jER (registered trademark)" 154 (manufactured by Mitsubishi Chemical Corporation) were put into a kneader, and the mixture was heated to 150°C while being kneaded, and kneaded at 150°C for 1 hour to obtain a transparent viscous liquid. After the viscous liquid was cooled to 60°C while being kneaded, 3.5 parts by mass of DICY7 (manufactured by Mitsubishi Chemical Corporation) as a curing agent and 3 parts by mass of DCMU99 (manufactured by Hodogaya Chemical Co., Ltd.) as a curing accelerator were blended, and the mixture was kneaded at 60°C for 30 minutes to prepare a thermosetting resin composition. This thermosetting resin composition was applied onto a release paper using a film coater to give a mass per unit area of ​​37 g / m 2 A film-shaped thermosetting resin (b-1) was prepared.

[0043] <Thermosetting resin containing cerium oxide particles (b-2)> 30 parts by mass of "jER (registered trademark)" 828 (manufactured by Mitsubishi Chemical Corporation), 20 parts by mass of "jER (registered trademark)" 1001 (manufactured by Mitsubishi Chemical Corporation), 15 parts by mass of "jER (registered trademark)" 1007 (manufactured by Mitsubishi Chemical Corporation), and 35 parts by mass of "jER (registered trademark)" 154 (manufactured by Mitsubishi Chemical Corporation) were put into a kneader, and the mixture was heated to 150°C while being kneaded, and kneaded at 150°C for 1 hour to obtain a transparent viscous liquid. After the viscous liquid was cooled to 60°C while being kneaded, 3.5 parts by mass of DICY7 (manufactured by Mitsubishi Chemical Corporation) as a curing agent, 3 parts by mass of DCMU99 (manufactured by Hodogaya Chemical Co., Ltd.) as a curing accelerator, and 3 parts by mass of cerium oxide particles with an average particle size of 25 nm were blended, and the mixture was kneaded at 60°C for 30 minutes. The mixture was then put into a roll mill to prepare a thermosetting resin composition. The thermosetting resin composition was applied onto a release paper using a film coater to give a mass per unit area of ​​37 g / m. 2 A film-shaped thermosetting resin (b-2) was prepared.

[0044] <Prepreg 1> Mass per unit area is 150g / m 2 A film-like thermosetting resin (b-1) was laminated on both sides of a sheet-like carbon fiber (TORAYCA (registered trademark) T700S-12K, manufactured by Toray Industries, Inc.)) aligned in one direction so as to form a prepreg 1. The resin was then impregnated at a roller temperature of 80° C. and a roller pressure of 0.25 MPa to produce the prepreg 1.

[0045] <Prepreg 2 containing cerium oxide> Mass per unit area is 150g / m 2 A film-like thermosetting resin (b-2) was laminated on both sides of a sheet-like carbon fiber (TORAYCA (registered trademark) T700S-12K, manufactured by Toray Industries, Inc.)) aligned in one direction so as to form a prepreg 2 containing cerium oxide particles. The resin was then impregnated at a roller temperature of 80° C. and a roller pressure of 0.25 MPa to produce a prepreg 2 containing cerium oxide particles.

[0046] <Cerium oxide dispersion> Cerium oxide particles having an average particle size of 25 nm were dispersed in a 1:1 mixture of N,N-dimethylacetamide and ethanol to a solution concentration of 2.9% by weight to prepare a cerium oxide dispersion.

[0047] <Polypropylene nonwoven fabric base material> A master batch was prepared by mixing 30% by mass of acid-modified polypropylene (Umex 1010 manufactured by Sanyo Chemical Industries, Ltd.) and 70% by mass of polypropylene (J229E manufactured by Mitsui Chemicals, Inc.). The master batch was melt-blown to a weight of 30 g / m. 2 A polypropylene nonwoven fabric substrate was prepared.

[0048] [Measurement example] <Proportion of cerium oxide particles present within 100 μm from the surface of fiber-reinforced resin molding> The fiber-reinforced resin molded bodies produced in each Example and Comparative Example were cut, and the cross sections were polished to prepare observation samples. The observation samples were scanned with SEM-EDX, and mapping images of cerium elements were obtained in each field of view for the area covering the thickness direction from one surface to the other surface. The area of ​​cerium elements in the entire thickness direction was calculated by image analysis focusing on the brightness of the obtained element mapping images. Next, the area of ​​cerium elements in the area within 100 μm from the surface was calculated in the same manner, and divided by the area of ​​cerium elements in the entire thickness direction to derive the proportion of cerium oxide particles present within 100 μm from the surface of the fiber-reinforced resin molded body.

[0049] <Cerium oxide shedding rate> The surface of the reinforced fiber resin molding produced in each Example and Comparative Example was scanned by XPS to measure the concentration (atmic%) of cerium element before the test. Then, the "Tape Test Method" according to JIS H 8504 (1999) was performed on the surface of the reinforced fiber resin molding. The surface after the "Tape Test Method" was scanned by XPS to measure the concentration (atmic%) of cerium element after the test. The measured value obtained was substituted into the following formula to derive the cerium oxide shedding rate. Fall-off rate [%] = (amount of cerium oxide particles (C) before test - amount of cerium oxide particles (C) after test) / (amount of cerium oxide particles (C) before test) x 100 <Logarithmic reduction in infection titer> Five samples, each 50 mm square, were cut out from five random points on the fiber-reinforced resin molded body produced in each Example and Comparative Example. Using the cut out samples, the log reduction in infectivity was calculated by the plaque method under conditions using influenza virus in accordance with ISO 21702.

[0050] <Distance between cerium oxide particles and reinforcing fibers> The fiber-reinforced resin molded bodies prepared in each Example and Comparative Example were cut, and the cross sections were polished to prepare observation samples. The observation samples were scanned with SEM-EDX, and a mapping image of the cerium element was obtained in the field of view near the surface. Next, 10 cerium oxide particles within 10 μm from the surface were randomly selected in the obtained image, and a straight line was drawn between the centroid of the cerium oxide particle and the centroid of the reinforcing fiber that was closest to the particle. If the cross section of the target reinforcing fiber was outside the obtained image, the centroid was defined by focusing on the part included in the obtained image. The distance between the surface and the straight line was measured, and the average value was calculated, which was used as the distance between the cerium oxide particle and the reinforcing fiber. If the number of cerium oxide particles within 10 μm from the surface was less than 10, the measurement was performed for all particles, and the average value was used as the distance between the cerium oxide particle and the reinforcing fiber.

[0051] [Example 1] Eight sheets of prepreg 1 were laminated so that the inclination of the fiber direction of the carbon fibers was 0° / 90° / 0° / 90° / 90° / 0° / 90° / 0° with respect to the reference direction. The dispersion was applied at 70 g / m2 to one surface of the obtained prepreg laminate. 2The mixture was sprayed so that the amount adhered was 100 μm, and then dried at 50°C for about an hour to obtain a preform. After drying, a hydraulic press with flat dies attached to the upper and lower platens was used to heat and pressurize the mixture at 150°C and a surface pressure of 1 MPa for 30 minutes to obtain a fiber-reinforced resin molded product. The proportion of cerium oxide particles present within 100 μm from the surface of the obtained fiber-reinforced resin molded product was 65%, the shedding rate of cerium oxide particles was 3%, the log reduction in infectivity was 1.1, and the distance between the cerium oxide particles and the carbon fibers (reinforced fibers) was 4.5 μm.

[0052] [Example 2] Eight sheets of prepreg 1 were laminated so that the inclination of the fiber direction of the carbon fibers was 0° / 90° / 0° / 90° / 90° / 0° / 90° / 0° with respect to the reference direction. Next, 70 g / m of the dispersion was applied to one surface of the polypropylene nonwoven fabric substrate. 2 The coating was sprayed so that the amount of the coating adhered was 100 μm, and the coating was dried at 50° C. for about 1 hour. After drying, the sheet substrate was laminated on the prepreg laminate so that the coated side of the sheet substrate was the surface, to obtain a preform. The preform was heated and pressed at 150° C. and a surface pressure of 1 MPa for 30 minutes using a hydraulic press machine with flat dies attached to the upper and lower platens, to obtain a fiber-reinforced resin molded body. The proportion of cerium oxide particles present within 100 μm from the surface of the obtained fiber-reinforced resin molded body was 95%, the cerium oxide particle shedding rate was 0%, the infectivity logarithmic reduction value was 1.4, and the distance between the cerium oxide particles and the carbon fiber, which is the reinforcing fiber, was 32.1 μm. In addition, when the cross section of the fiber-reinforced resin molded body was observed, the sheet substrate formed a layer and was impregnated up to the carbon fiber.

[0053] [Example 3] Eight sheets of prepreg 1 were laminated so that the inclination of the fiber direction of the carbon fiber was 0° / 90° / 0° / 90° / 90° / 0° / 90° / 0° with respect to the reference direction. Next, a glass fiber nonwoven fabric base material (basis weight: 30 g / m 2 ) was prepared, and the dispersion was applied to one surface at 70 g / m 2The coating was sprayed so that the amount of the coating adhered was 100 μm, and the coating was dried at 50°C for about 1 hour. After drying, the sheet substrate obtained was laminated on a prepreg laminate so that the coated side of the sheet substrate became the surface, to obtain a preform. The obtained preform was heated and pressed at 150°C and a surface pressure of 1 MPa for 30 minutes using a hydraulic press with flat dies attached to the upper and lower platens, to obtain a fiber-reinforced resin molded body. The proportion of cerium oxide particles present within 100 μm from the surface of the obtained fiber-reinforced resin molded body was 90%, the dropout rate of cerium oxide particles was 15%, the log reduction in infectivity was 1.2, and the distance between the cerium oxide particles and the glass fiber reinforcing fiber was 3.9 μm.

[0054] [Comparative Example 1] A preform was obtained by laminating eight prepregs 2 so that the inclination of the fiber direction of the carbon fibers was 0° / 90° / 0° / 90° / 90° / 0° / 90° / 0° with respect to the reference direction. The obtained preform was heated and pressed at 150°C and a surface pressure of 1 MPa for 30 minutes using a hydraulic press machine with flat dies attached to the upper and lower platens, to obtain a fiber-reinforced resin molded product. The proportion of cerium oxide particles present within 100 μm from the surface of the obtained fiber-reinforced resin molded product was 9%, the shedding rate of cerium oxide particles was 0%, and the infectivity log reduction value was 0.1. [Explanation of symbols]

[0055] 1 Fiber-reinforced resin molding 2 Anti-pathogen area 3 Reinforced Fiber (A) 4. Matrix resin (B) 5 Compound (C) 6 Thermoplastic resin (D)

Claims

1. A fiber-reinforced resin molding comprising a reinforcing fiber (A), a matrix resin (B), and a compound (C) having antibacterial or antiviral properties, A fiber-reinforced resin molding having an antipathogenic region in which at least a portion of the compound (C) is exposed on a surface of the fiber-reinforced resin molding.

2. The fiber-reinforced resin molding according to claim 1, wherein 50 to 100% of the compound (C) is present within 100 μm from the surface of the molding in a cross section of the antipathogenic region.

3. The fiber-reinforced resin molding according to claim 1 or 2, wherein the antipathogenic region has a dropout rate of the compound (C) of 5% or less as tested in accordance with JIS H 8504 (1999).

4. The fiber-reinforced resin molding according to claim 1 or 2, wherein a thermoplastic resin (D) is further exposed in the antipathogenic region.

5. The fiber-reinforced resin molding according to claim 4, wherein a layer composed of the thermoplastic resin (D) and the compound (C) is formed on a surface layer in the antipathogenic region.

6. 3. The fiber-reinforced resin molding according to claim 1, wherein the distance between the compound (C) exposed from the matrix resin (B) and the reinforcing fiber (A) in the cross section of the antipathogenic region is 0.05 μm or more and 5.00 μm or less.

7. The fiber-reinforced resin molding according to claim 1 or 2, wherein the antipathogenic region has an infectivity log reduction value of 1.0 or more as measured in accordance with ISO 21702.

8. The fiber-reinforced resin molding according to claim 1 or 2, wherein the compound (C) is a metal-based compound (c).

9. The fiber-reinforced resin molding according to claim 8 , comprising an inorganic compound carrying a metal ion as the metal-based compound (c).

10. The fiber-reinforced resin molding according to claim 8 , comprising cerium oxide as the metal-based compound (c).

11. A step of preparing an intermediate substrate including reinforcing fibers (A) and a matrix resin (B); A step of obtaining a preform having a dispersion of a compound (C) having antibacterial or antiviral properties disposed on the surface of the intermediate substrate by the following method (I) or (II); (I) A dispersion obtained by dispersing the compound (C) in a solvent having a solubility in the matrix resin (B) is adhered to at least a part of the surface of the intermediate substrate. (II) A sheet substrate containing the thermoplastic resin (D) having the compound (C) adhered thereto is laminated on at least a portion of the surface of the intermediate substrate. a step of molding the preform by heating and pressing; A method for producing a fiber-reinforced resin molded body comprising the steps of:

Citation Information

Patent Citations

  • Antibacterial coating agent resin composition

    JP1999228908A

  • Antibacterial composite molding and its manufacturing method

    JP2023054044A

  • Radiographic apparatus and manufacturing method thereof

    JP2023071243A